USULAN PENINGKATAN KUALITAS PELAYANAN YANG MEMPENGARUHI LOYALITAS PELANGGAN TRIANGLE COFFEE CARAVAN BERDASARKAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) DAN REGRESI LINEAR - RODIANSYAH, BILLY; MUKTI, YOANITA YUNIATI (e-Proceeding FTI, 2024)
The decline in the turnover of the Triangle Coffee Caravan was partly due to the quality of the facilities, the quality of the service, and the increase in competitors. Triangle Coffee Caravan has made several improvement efforts but the number of customers has not increased significantly.The research is aimed at producing a proposed design for improving service quality in increasing customer loyalty inTriangle Coffee Caravan. Quality measurement was carried out using the service quality dimension and the results of distributing questionnaires obtained data from 99 respondents regarding the level of interest, level of satisfaction, and customer loyalty.The results of simple regression calculations show that customer satisfaction has quite an influence on the level of loyalty. The priority of proposals for increasing customer satisfaction is carried out using Importance Performance Analysis. Proposed implementation of quality improvement includes Wi-fi network attributes. menu price suitability attribute. Attributes of coffee shop employees recommend best seller products. Attributes of coffee shop employees provide fast service. Attributes of coffee shop employees provide assistance when there are complaints. parking area security attributes. Abstrak Penurunan omset Triangle Coffee Caravan diantaranya disebabkan oleh kualitas fasilitas, kualitas layanan, dan bertambahnya pesaing. Pihak Triangle Coffee Caravan telah melakukan beberapa upaya perbaikan namun jumlah pelanggan tidak mengalami peningkatan yang signifikan. Penelitian ditujukan untuk menghasilkan rancangan usulan peningkatan kualitas layanan dalam meningkatkan loyalitas pelanggan di Triangle Coffee Caravan. Pengukuran kualitas dilakukan menggunakan dimensi service quality dan hasil penyebaran kuesioner diperoleh data dari 99 responden terkait tingkat kepentingan, tingkat kepuasan, dan loyalitas pelanggan. Hasil perhitungan regresi sederhana menunjukkan kepuasan pelanggan memiliki cukup pengaruh terhadap tingkat loyalitas. Prioritas usulan peningkatan kepuasan pelanggan dilakukan menggunakan Importance Performance Analysis. Usulan implementasi peningkatan kualitas antara lain atribut jaringan Wi-fi. atribut kesesuaian harga menu. atribut karyawan coffee shop merekomendasi produk best seller. atribut karyawan coffee shop memberikan pelayanan secara cepat. atribut karyawan coffee shop memberikan bantuan apabila terdapat keluhan. atribut keamanan area parkir.